Efficacy of Endoscopic Mucosal Resection for Management of Small Duodenal Neuroendocrine Tumors. Issue 5 (October 2015) - Shroff, Sagar R.; Kushnir, Vladimir M.; Wani, Sachin B.; Gupta, Neil; Jonnalagadda, Sreenivasa S.; Murad, Faris; Early, Dayna S.; Mullady, Daniel K.; Edmundowicz, Steven A.; Azar, Riad R.
<x xml:space="preserve">Abstract</x> Background: Endoscopic mucosal resection (EMR) for small (<20 mm) duodenal neuroendocrine tumors (NETs) remains controversial because of their rarity. Materials and Methods: This is a retrospective cohort study of patients with surgically or endoscopically resected duodenal NETs from 2001 to 2011. The primary outcome is the rate of disease-free status following resection. A secondary outcome is the sensitivity of endoscopic ultrasound (EUS) in determining NET appropriateness for EMR. Results: Thirty patients underwent resection of duodenal NETs (EMR 20, surgery 10). Tumor was present at the margins in 40% of EMR-resected NETs and 10% of surgically resected NETs. Five patients who underwent EMR had residual disease treated with repeat EMR (3) and surgery (2). EUS demonstrated 96% sensitivity in determining lesions limited to the submucosa. Conclusions: EMR for small duodenal NETs can be a safe and effective alternative to surgery in carefully selected patients. EUS is a useful adjunct in determining depth of invasion for duodenal NETs.